Rethinking Institutional Reforms in the Philippine Housing Sector - Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2002)
Why have housing reforms failed to achieve the desired improvements in housing in the Philippines? A review of trends in government housing strategies shows that while many problems in housing are linked to institutional barriers in the land and financial markets, government reforms focused on operational and program specific issues. While these reforms may be needed, they can only be effective if basic institutional issues are first addressed. The paper suggests that the efficient functioning of the land and financial markets is a necessary condition for the efficient functioning of the housing market. This requires government to undertake major reforms in land regulations and land administration infrastructure including the implementation of an effective real property tax system. On housing finance, government should re-adopt the financial reform concept developed in 1997 with assistance from the World Bank that calls for a clear separation of subsidy mechanisms from transactions in housing finance and to take initial steps to reduce subsidy that goes to high and middle-income housing markets. These reforms would also warrant reforms in the governance structure of housing delivery. Complete devolution of housing delivery functions to the local government is necessary. On the other hand, national government concerns will primarily be on providing the policy environment and housing subsidy management. These concerns may only require the creation of a corporate organization rather than a Department of Housing and Urban Development.
Keywords: 330; housing sector; institutional reforms; Wohnung; Wohnungsbau; Wohnungspolitik; Reform; Philippinen